Economic Dimensions of the Bioeconomy: Case Study of Iceland - Elísabet Kemp Stefánsdóttir 1988- (2014)
The term bioeconomy has attracted increasing attention over the last decade. It is considered to encompass all economic activity connected with the utilisation of renewable biological resources. The renewable biological resources are of particular interest since they offer sustainable utilisation, which ensures non-decreasing welfare for future generations. The objectives with this analysis were to define the bioeconomy, consider the economic dimensions of the bioeconomy, and use these to analyse the Icelandic bioeconomy. A literary review of the bioeconomy was performed to consider the origin of the term and find a definition. The definition chosen is in synchrony with previous work undertaken by the European Commission and underlines the connection to renewable biological resources. Economic theory was used to propose indicators for the economic dimensions of the bioeconomy, which are value added, part of GDP, labour and capital productivity, exports and part of total export value. The theory of base industries was used to consider if these indicators underestimated the contribution of the bioeconomy to the economy. Principal components analysis and cluster analyses were then used to decide if the economic dimension could be reduced. The analyses indicate that the economic dimension could be reduced to two. The results show that the bioeconomy in Iceland has a direct contribution of 13% to GDP, where the biggest contribution is from the fishing industry. It has previously been stated that the fishing industry is a base industry in Iceland, and has a total contribution of 26% to GDP. This indicates that the total contribution of the bioeconomy to GDP is around 30%. The Icelandic bioeconomy is a relatively big part of the economy compared to other Nordic countries. The bioeconomies of Iceland, the Faroe Islands and Greenland seem to differ from the bioeconomies of other Nordic countries.